Predicting the lifetime of CPVC under increasing temperature and crosshead speed - Abderrahim Khtibari; Abdelkrim Kartouni; Mohamed Elghorba; Abderrazak En-Naji (Fracture and Structural Integrity)
The aim of this paper is to characterize the mechanical characteristics of chlorinated PVC (CPVC). Tensile tests were carried on the compounds at different temperatures ranging from -20 to 90C and crosshead speeds from 5 to 500 mm/min. The results were analyzed to determine how crosshead speed and temperature affected on the mechanical characteristics of CPVC specimens. Two damage models are then developed, one model obtained by adapting the unified theory version and the other quasi-experimental static model based on ultimate stress. These models allow us to evaluate the damage evolution of CPVC samples and to determine the safety and maintenance intervals of this material.